Master the TOEFL test - Sullivan, Patricia Noble; Brenner, Gail Abel.; Zhong, Grace Yi Qiu.; Nguyễn Văn Phước; Ban biên dịch First News. (Tp.HCM : Nxb Trẻ, 2001)
The test of English as a foreign language, Sample questions and test - talking strategies, Six practice Toefl tests, Tapescripts for practice test.
Keywords: English language; Toefl; English language -- Tests; English language -- Study and teaching -- Textbooks for foreign speakers